Perfectionism, Economic (Dis)Incentives, and Political Coercion - Moked, Oran (Les ateliers de l'éthique / The Ethics Forum, 2009)
May a government attempt to improve the lives of its citizens by promoting the activities it deems valuable and discouraging those it disvalues? May it engage in such a practice even when doing so is not a requirement of justice in some strict sense, and even when the judgments of value and disvalue in question are likely to be subject to controversy among its citizens? These questions have long stood at the center of debates between political perfectionists and political neutralists. In what follows I address a prominent cluster of arguments against political perfectionism—namely, arguments that focus on the coercive dimensions of state action. My main claim is simple: whatever concerns we might have about coercion, arguments from coercion fall short of supporting a thoroughgoing rejection of perfectionism, for the reason that perfectionist policies need not be coercive. The main body of the paper responds, however, to several neutralist challenges to this last claim.